Analysis of Instructional Questions in English Textbook in Senior High School - Awalo, Setni Chintia; Oroh, Elisabeth Z.; Wongkar, Yapi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research to analysis the occurrence of instructional questions pertaining to listening, reading, speaking and writing activities in the Bahasa Inggris course book designed for Class X students in SMA/MA/SMK/MAK. The research also sought to ascertain the primary cognitive component of the instructional questions in the textbook, whether it prioritized High Order Thinking Skills (HOTS) or Low Order Thinking Skills (LOTS). A comprehensive content analysis was performed on each of the nine chapters of the textbook in order to investigate the research issues. Moreover, the focus of the research was primarily on instructional questions. The instructional questions were collected, listed, and analysed according to Bloom’s Taxonomy of cognitive domains. The researcher calculated the proportion and frequency of the questions related to various levels of cognition that were included in each chapter of the textbook. The study used descriptive statistics to provide a thorough synopsis of the basic attributes of the data. The results revealed that there were a combined total of 85 instructional questions, including skills related to listening, reading, speaking and writing. The listening exercises had the lowest number of instructional questions, consisting of just 2 questions. Conversely, reading activities had the greatest quantity of instructional questions, totalling 43. The instructional questions in speaking and writing tasks were rather frequent, with 22 and 18 questions, respectively. After classifying the instructional questions in all activities, it became clear that the bulk of those questions (a total of 67) focused heavily on LOTS.